2020
DOI: 10.3390/ijms21030785
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Dissection of Xanthomonas oryzae pv. oryzae Responsive MicroRNAs in Rice

Abstract: MicroRNAs (miRNAs) are crucial player in plant-pathogen interaction. While the evidence has demonstrated that rice miRNAs mediate immune response to pathogens invasion, the roles of miRNAs on Xanthomonas oryzae pv. oryzae (Xoo) attack remain be in place. Herein, we monitored the responsive changes of rice miRNAs at 0, 8, 24 h across Xoo strain PXO86 infection in its compatible rice variety IR24 and incompatible variety IRBB5 by small RNA sequencing, and the genes targeted by miRNAs were also detected via degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…We found that 24 nt miRNAs were the most frequent form, followed by 21 nt sRNAs. These patterns of length distribution have also been identified in rice and barley (Hackenberg et al, 2015;Jia et al, 2020). Moreover, the first position in 18-25 nt miRNAs was predominantly U.…”
Section: Discussionsupporting
confidence: 58%
“…We found that 24 nt miRNAs were the most frequent form, followed by 21 nt sRNAs. These patterns of length distribution have also been identified in rice and barley (Hackenberg et al, 2015;Jia et al, 2020). Moreover, the first position in 18-25 nt miRNAs was predominantly U.…”
Section: Discussionsupporting
confidence: 58%
“…To observe whether the transcriptional regulatory events occurred in rice-Xoo interactions, we checked the expression pro les of OsPR1a and OsPR1b by RT-qPCR using speci c primers (Table S6) at different time points post inoculation (hpi) with PXO99 A . The levels of the OsPR1a and OsPR1b transcripts showed a similar induction pro le (Figure S1), which is consistent with the defense-responsive expression in previous report (Jia et al 2020). Their transcript levels slightly induced at 2 hpi and 6 hpi or markedly increased at 12 hpi and decreased drastically at 24 hpi (Figure S1).…”
Section: Discovery and Characteristic Of Circrnas In Rice Leavessupporting
confidence: 90%
“…These observations are incompatible with the possibility that xisRNA loci correspond to canonical MIRNA genes. Previous work has identified differentially accumulating rice miRNA during Asian Xoo infection (21, 22), it was therefore surprising that no xisRNA locus corresponded to a MIRNA . This may be due to differences in the way rice responds to Asian versus African Xoo strains or in sRNA-seq data analysis methods.…”
Section: Discussionmentioning
confidence: 99%
“…xisRNA loci correspond to canonical MIRNA genes. Previous work has identified differentially accumulating rice miRNA during Asian Xoo infection (21,22), it was therefore surprising that no…”
Section: How Well Do Xisrnas Fit In Canonical Classes Of Plant Srnas?mentioning
confidence: 99%
See 1 more Smart Citation